2011
DOI: 10.1889/jsid19.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Control of subjective depth on 3‐D displays by a quantified monocular depth cue

Abstract: This paper considers the architecture and the effectiveness of new algorithms that control the subjective depth on 3-D displays by modulating the contrast of stereoscopic pictures on the basis of a quantified monocular depth cue. First, a psychophysical experiment to quantify the relationship between contrast and subjective depth was conducted. This experimental result shows that the higher the contrast, the nearer the object will be perceived, corresponding to the qualitative relationship. Second, this result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Our conventional algorithm for still pictures consists of the following six steps [1]: luminance calculation, contrast analysis, frequency analysis, depth estimation, modulation-amplitude calculation, and contrast modulation. In the first step, luminance of each input picture was calculated.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Our conventional algorithm for still pictures consists of the following six steps [1]: luminance calculation, contrast analysis, frequency analysis, depth estimation, modulation-amplitude calculation, and contrast modulation. In the first step, luminance of each input picture was calculated.…”
Section: Overviewmentioning
confidence: 99%
“…Then, observers viewed the pictures and compared their depth ranges between the nearest and the furthest regions. Finally, they answered a score based on 5-scale evaluation terms [1].…”
Section: Subjective Assessment 41 Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujisaki et al . examined individual differences in use of disparity information in currently prevailing 3D graphics environments designed to give observers rich depth perception conveyed by a combination of binocular disparity and monocular pictorial cues . The resulting visual displays used simple 3D graphic stimuli containing shading and binocular disparity.…”
Section: Introductionmentioning
confidence: 99%
“…Fujisaki et al examined individual differences in use of disparity information in currently prevailing 3D graphics environments 10,11 designed to give observers rich depth perception conveyed by a combination of binocular disparity and monocular pictorial cues. 12 The resulting visual displays used simple 3D graphic stimuli containing shading and binocular disparity. Fujisaki et al demonstrated that 30% of young observers, aged 19-25 years, relied only on information from shading, rather than from disparity, to perceive the depth of the 3D stimuli even when the stimuli contained larger disparities than stimuli the same observers were able to discriminate in a Titmus stereoscopic test.…”
Section: Introductionmentioning
confidence: 99%